2017
DOI: 10.1007/s00484-017-1337-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geomagnetic activity and atmospheric pressure in hypertensive adults

Abstract: We performed a study of the systolic and diastolic arterial blood pressure behavior under natural variables such as the atmospheric pressure and the horizontal geomagnetic field component. We worked with a group of eight adult hypertensive volunteers, four men and four women, with ages between 18 and 27 years in Mexico City during a geomagnetic storm in 2014. The data was divided by gender, age, and day/night cycle. We studied the time series using three methods: correlations, bivariate analysis, and superpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…In our study, the daily mean PRE was low (945.06hPa) in warm months but high (955.34hPa) in cold months (data not shown). Although some studies found a correlation between PRE and blood pressure, 28 , 29 the specific biological mechanism of PRE on ICH occurrence remains to be clarified. 15 …”
Section: Discussionmentioning
confidence: 97%
“…In our study, the daily mean PRE was low (945.06hPa) in warm months but high (955.34hPa) in cold months (data not shown). Although some studies found a correlation between PRE and blood pressure, 28 , 29 the specific biological mechanism of PRE on ICH occurrence remains to be clarified. 15 …”
Section: Discussionmentioning
confidence: 97%
“…только атмосферного давления (Р атм ) и его изменчивости, но без учета влияния температуры [Dockery et al, 1999;Azcárate, Mendoza, 2017];…”
Section: фоновые вариации погоды и госпитализацииunclassified
“…Вторая группа статей, сравнительно немногочисленная, показывает существование значимых корреляций между суточными вариациями Р атм и числом госпитализаций по поводу острого инфаркта миокарда (ИМ) и инсульта , а также изменениями АД, частоты сердечных сокращений (ЧСС) и насыщения крови кислородом у больных и пожилых людей [Dockery et al, 1999;Azcárate, Mendoza, 2017].…”
Section: фоновые вариации погоды и госпитализацииunclassified
“…Geomagnetic storms of remarkable intensity may have a potential effect on many aspects of human life, including health effects due to radiation hazards, disruption of electrical systems like communications appliances, navigation systems, satellites… The biological mechanisms altered by geomagnetic storms are explored in ref. 10 , and geomagnetic activity has been recently related to several human conditions as hypertension 11 , multiple sclerosis [12][13][14] or cancer 15 . However, it is still unclear to what extend and under what threshold these health effects appear or the risk increases.…”
Section: Effects Of Geomagnetic Stormsmentioning
confidence: 99%